The benefits of sports for the physical and mental health of adolescents - Maria Stamova Vakrilova Becheva; Angelina Georgieva Kirkova-Bogdanova; Krasimira Milcheva Kazalakova; Stefka Achkova Ivanova (Pensoft Publishers, 2023)
A healthy lifestyle is the main expression of positive health behavior. Movement is a natural need of every child and is a basic preventive tool for strengthening children's health. Sport is a complex process that improves the qualities of movements, strengthens the muscles of the body and forms physical endurance through its positive influence on all organs and systems. Sports activities have a beneficial effect on the psyche and personality of adolescents and are defined as the main factor for maintaining, preserving and improving health and a healthy lifestyle. In most European countries, the teaching methodology is aimed at finding the meaning and encouraging the desire of each student to engage in regular physical activity. The article aims to familiarize the audience with the impact of sports on various organs and systems, with the benefits for the physical and mental health of adolescents from sports activities, as well as to provide information on recommendations for the correct choice of sports depending on the constitution and disposition of adolescents.